2007
DOI: 10.1182/blood-2007-01-067918
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis is a natural stimulus of IL6R shedding and contributes to the proinflammatory trans-signaling function of neutrophils

Abstract: Interleukin 6 (IL6) trans-signaling has emerged as a prominent regulator of immune responses during both innate and acquired immunity. Regulation of IL6 trans-signaling is reliant upon the release of soluble IL6 receptor (sIL6R), which binds IL6 to create an agonistic IL6/sIL6R complex capable of activating cell types that would not normally respond to IL6 itself. Here we show that intrinsic and extrinsic apoptotic stimulation by DNA damage, cytokine deprivation, and Fas stimulation promotes shedding of sIL6R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
255
3
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 291 publications
(279 citation statements)
references
References 50 publications
16
255
3
3
Order By: Relevance
“…Animals that have been depleted of neutrophils showed no increase in sIL6R levels in air pouches, and these changes were associated with a marked reduction in the number of infiltrating mononuclear cells. 27 We suggest that sIL6R liberated from the infiltrating neutrophil population is required to drive the recruitment of inflammatory mononuclear cells to the site of inflammation. 27 Because we were especially interested in the influence of IL6 transsignaling on monocyte recruitment during the late phase of acute inflammation, we next evaluated the inflammatory regulation of leukocytes in the opt_sgp130Fc transgenic mice.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…Animals that have been depleted of neutrophils showed no increase in sIL6R levels in air pouches, and these changes were associated with a marked reduction in the number of infiltrating mononuclear cells. 27 We suggest that sIL6R liberated from the infiltrating neutrophil population is required to drive the recruitment of inflammatory mononuclear cells to the site of inflammation. 27 Because we were especially interested in the influence of IL6 transsignaling on monocyte recruitment during the late phase of acute inflammation, we next evaluated the inflammatory regulation of leukocytes in the opt_sgp130Fc transgenic mice.…”
mentioning
confidence: 88%
“…27 We suggest that sIL6R liberated from the infiltrating neutrophil population is required to drive the recruitment of inflammatory mononuclear cells to the site of inflammation. 27 Because we were especially interested in the influence of IL6 transsignaling on monocyte recruitment during the late phase of acute inflammation, we next evaluated the inflammatory regulation of leukocytes in the opt_sgp130Fc transgenic mice.In vitro experiments revealed that at least a 10-fold molar excess of sgp130Fc to IL6/sIL6R is sufficient to completely block IL6-transsignaling. 24 Air pouches from transgenic animals contained sgp130Fc protein in the range of 3 g, which is a 100-fold molar excess of sgp130Fc to IL6/sIL6R and therefore should be sufficient to block IL6 transsignaling-mediated processes in vivo during acute inflammation ( Figure 4A).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…55 In vivo trans-signalling dramatically increases the number of potentially IL-6 responsive cells, which are otherwise limited by missing complete IL-6R expression: during acute inflammatory events, infiltrating neutrophils can become a source of sIL-6R through its shedding from the membranes of both living and apoptosing cells. 56 In an in vivo experimental model of myosininduced myositis, IL-6 À/À mice were disease free, with no clinical sign of muscle weakness, or any microscopic evidence of neuromuscular infiltration. 57 In polymyositis biopsies, only those myofibres that were invaded and destroyed by mononuclear cells express high levels of IL-6, MCP-1 and ICAM-1.…”
Section: Muscle Cells Recruit Leukocytesmentioning
confidence: 99%